Ischemic Stroke in a patient with Essential Thrombocythemia: Case Report - Moniruzzaman, Md; Chandra, Subir; Sayeed, SK Jakaria Been (Journal of Medicine, 2022)
Essential thrombocythemia represents a rare risk factor for ischemic stroke. Uncontrolled proliferation of megakaryocytes sustained increases circulating platelet count and thrombotic risk. Many patients suffering from the disease may have no symptoms for a long time. We present a case of 60 year old lady with ischemic stroke who was a known case of essential thrombocythemia. And the cerebrovascular event was the complication of essential thrombocythemia as she quit treatment. J MEDICINE 2022; 23: 169-172